Association of dispatcher-assisted cardiopulmonary resuscitation with initial shockable rhythm and survival after out-of-hospital cardiac arrest. (February 2022) - Goto, Yoshikazu; Funada, Akira; Maeda, Tetsuo; Goto, Yumiko
Abstract : Background and importance: Bystander cardiopulmonary resuscitation (CPR) and initial shockable rhythm are crucial predictors of survival after out-of-hospital cardiac arrest (OHCA). However, the relationship between dispatcher-assisted CPR (DA-CPR) and initial shockable rhythm is not completely elucidated. Objective: To examine the association of DA-CPR with initial shockable rhythm and outcomes. Design, setting and participants: This nationwide population-based observational study conducted in Japan included 59 688 patients with witnessed OHCA of cardiac origin after excluding those without bystander CPR. Patients were divided into DA-CPR ( n = 42 709) and CPR without dispatcher assistance (unassisted CPR, n = 16 979) groups. Outcome measures and analysis: The primary outcome measure was initial shockable rhythm, and secondary outcome measures were 1-month survival and neurologically intact survival. A Cox proportional hazards model adjusted for collapse-to-first-rhythm-analysis time and multivariable logistic regression models were used after propensity score (PS) matching to compare the incidence of initial shockable rhythm and outcomes, respectively. Main results: Among all patients (mean age 76.7 years), the rates of initial shockable rhythm, 1-month survival and neurologically intact survival were 20.8, 10.7 and 7.0%, respectively. The incidence of initial shockable rhythm in the DA-CPR group (20.4%, 3462/16 979) was significantly higher than that in the unassisted CPR group (18.5%, 3133/16 979) after PS matching ( P < 0.0001). However, no significant differences were found between the two groups with respect to the incidence of initial shockable rhythm in the Cox proportional hazards model [adjusted hazard ratio of DA-CPR for initial shockable rhythm compared with unassisted CPR, 0.99; 95% confidence interval (CI), 0.97–1.02, P = 0.56]. No significant differences were observed in the survival rates in the two groups after PS matching [10.8% (1833/16 979) vs. 10.3% (1752/16 979), P = 0.16] and neurologically intact survival rates [7.3% (1233/16 979) vs. 6.8% (1161/16 979), P = 0.13]. The multivariable logistic regression model showed no significant differences between the groups with regard to survival (adjusted odds ratio of DA-CPR compared with unassisted CPR: 1.00; 95% CI, 0.89–1.13, P = 0.97) and neurologically intact survival (adjusted odds ratio: 1.12; 95% CI, 0.98–1.29, P = 0.14). Conclusion: DA-CPR after OHCA had the same independent association with the likelihood of initial shockable rhythm and 1-month meaningful outcome as unassisted CPR. Abstract : Supplemental Digital Content is available in the text.